9514 1404 393
Answer:
(x, y) ⇒ (x -5, y +3)
Explanation:
Pick a point on the original polygon. The extreme left point (at (1, 0)) will do.
Locate the corresponding image point on ABCDE. (It is point B(-4, 3).) Using coordinates, or counting grid squares, determine what must be added to the original point to get the image point.
Here, that addition is 5 squares left and 3 squares up:
image - original = (-4, 3) -(1, 0) = (-5, 0)
So, the transformation rule adds -5 to each x-coordinate and 3 to each y-coordinate:
(x, y) ⇒ (x -5, y +3)